Working Memory Predicts Hypothalamus-Pituitary-Adrenal Axis Response to Psychosocial Stress in Males - Lin, Li; Wu, Jianhui; Yuan, Yiran; Sun, Xianghong; Zhang, Liang (Frontiers in Psychiatry, 2020)
The hypothalamic-pituitary-adrenocortical (HPA) function is crucial for adaptation to stress and recovery of homeostasis. Physiological alteration in the HPA axis has been shown to play a pivotal role in the generation of stress-related disorders. A growing number of studies have begun to identify which variables are possible to predict individual HPA response and associated stress vulnerability. The current study investigated the relationship between working memory and the subsequent magnitude of HPA response to psychosocial stress in a nonclinical population. Working memory was assessed utilizing an n-back task (2/3-back) in thirty-nine healthy young men, whose electroencephalograms were recorded. The HPA response was measured using the percentage increase in cortisol to an acute psychosocial stress protocol called the Trier Social Stress Test (TSST). Our results show that longer reaction time and smaller amplitude of P2 predict a relatively lower HPA response to stress. Our study provides new insights into how neurocognitive factors can be used to predict HPA response to acute stress.